“I Understood you, but there was this Pronunciation Thing…”: L2 Pronunciation Feedback in English/French Tandem Interactions - Horgues, Céline; Scheuer, Sylwia (Research in Language, 2014)
The role of corrective feedback (CF) in L2 development has been the topic of much discussion in SLA literature (see for example Sheen and Ellis 2011 for a recent overview). Researchers have focused their attention on CF provided either by language teachers or by fellow L2 learners, whereas relatively little is known about phonetic feedback offered in a non-institutional setting during peer-to-peer native/non-native interactions as is the case with tandem language learning. Tandem language exchanges represent a special learning environment, as each participant takes turns being the native and the non-native side of the dialogue. Thus, in contrast to the typical L2 learning setting, the hierarchical structure between the participants is fluid: the expert-novice power relationship evolves as the meeting progresses and the conversation switches from one language to the other. In order to see how the distinguishing characteristics of tandem learning (such as solidarity and reciprocity) shape the process of L2 phonetic development in their own specific ways, we collected an English-French Tandem Corpus as part of the SITAF project (Spécificités des Interactions verbales dans le cadre de Tandems linguistiques Anglais-Français), launched at the University of Sorbonne Nouvelle-Paris 3 in October 2012. We gathered linguistic data – both video and audio recorded – from face-to-face conversational exchanges held by 21 pairs of undergraduate students, with each ‘tandem’ consisting of a native speaker of English and a native speaker of French. The dialogues and reading passages were recorded on two occasions separated by a 3-month interval. The present paper offers a preliminary analysis of L2 pronunciation feedback on several renditions of the same text (The North Wind and the Sun), given to the French speakers by their English tandem partners. The passage was produced by each French participant three times: (1) during the ‘monitored’ reading, which was supervised by the English-speaking partner and which led to (2) the ‘second reading’ in the course of the first recording session, and then (3) the ‘final reading’ performed during the second recording session 3 months later. Data analysis will allow us to address the following questions relating to the study of phonetic corrective feedback: - What is corrected by the native-speaking partner (henceforth NS)? Segmental or prosodic errors? Phonemic or allophonic deviations? - What is the corrective strategy adopted by the NS? Is it explicit correction, recast, or elicitation? - What is the learner’s uptake after receiving feedback? We hope that our data brings a valuable and fairly unique contribution to SLA research, helping to establish which errors get corrected and how it may have implications for setting priorities in L2 pronunciation teaching.